My Contemporaries In Fiction - Murray, David Christie, 1847-1907 (Salt Lake City, UT : Project Gutenberg, 2007)
"My Contemporaries In Fiction" by David Christie Murray is a collection of critical essays written in the late 19th century. The book examines the works and contributions of notable contemporary authors, including Charles Dickens, Thomas Hardy, and Rudyard Kipling. Murray presents his perspectives on these writers, assessing both their literary impact and the quality of their work, while hoping to provide insights to readers on contemporary fiction. The opening of the work establishes Murray's intention to critique the literary field of his time, addressing the over-praise and lack of critical depth in contemporary literary critiques. He expresses concern about modern critics who excessively elevate mediocre writers while diminishing the value of established masters like Dickens. Furthermore, he offers a personal insight into his own role as a writer and critic, assuring readers of his sincerity and commitment to presenting an honest assessment of the art of fiction. The opening sets a reflective tone, asserting the importance of honest criticism in stabilizing the literary landscape. (This is an automatically generated summary.)
First, the critics, and then a word on Dickens -- Charles Reade -- Robert Louis Stevenson -- Living masters, Meredith and Hall Caine -- Living masters, Rudyard Kipling -- Under French encouragement,Thomas Hardy -- Under French encouragement, George Moore -- Mr. S.R. Crockett, Ian Maclaren -- Dr. Macdonald and Mr. J.M. Barrie -- The problem seekers, sea captain and land captain -- Miss Marie Corelli -- The Americans -- The young romancers.
Release date is 2007-08-01
Produced by David Widger
Keywords: English fiction -- 19th century -- History and criticism